Integrasi Pariwisata Halal di Kota Malang - Mochamad Novi Rifa’i (Universitas Muhammadiyah Malang, 2019)
Malang City is one of the seven cities in Indonesia which became a pilot project for halal tourism. Therefore the aims of this study are to analyze the potential of sharia tourism in Malang City and develop the concept of integration of location and halal tourism information in Malang City. This study is a qualitative-descriptive, with the model of data analysis using Spradley’s model, in which after determining the standard of halal tourism, then proceeding to inventory halal tourism destination in Malang and make the concept of integration between location and halal tourism information in Malang. The result of this study shows that; first, that halal tourism is tourism which in its presentation takes into account the factors of Madiyah (material) and Adabiyah (process) in accordance with the sharia. Halal tourism destinations in Malang including education, lodging, culinary, thematic, religious, historical and cultural tourism. Second, the integration of tourism in Malang can be done by making a memorandum of understanding between stakeholders to collaborate providing the best information and services for all tourists.